Rekonstruksi Kurikulum Pendidikan Agama Islam Berbasis Kebutuhan Zaman - Siti Asiah Nurfadillah; Iskandar Mirza; Akhmad Rozikin (Advances In Education Journal, 2026)
The digital era has fundamentally changed the way students learn, interact, and understand the world around them. Islamic Religious Education (PAI) curriculum currently faces significant challenges in remaining relevant to the needs of today's students. This study aims to analyze the reconstruction model of the PAI curriculum based on contemporary needs, focusing on the integration of digital literacy and character reinforcement. This research uses a qualitative method with a library research approach, collecting data from various scientific journals, books, and relevant previous studies. The results indicate that an ideal PAI curriculum reconstruction includes three main aspects: 1) integration of technology and digital literacy in learning, 2) reinforcement of student character through a values-based approach, and 3) the strategic role of PAI teachers as facilitators and mentors in the digital era. The implication of this research emphasizes the importance of adaptive and responsive curriculum transformation to address the challenges of the times without abandoning the essential values of Islamic teachings.